Subcellular Distribution and Chemical Form of Cadmium in Bean Plants - Weigel, Hans J. (1980)
The subcellular distribution and chemical form of Cd in bean plants grown in nutrient solutions containing Cd were investigated. Cd was accumulated mainly in roots and to a minor extent in leaves. Subcellular fractionation of Cd-containing tissues (pH 7.5) showed that more than 70% of the element was localized in the cytoplasmic fraction in roots as well as in leaves. Little Cd (8 to 14%) was bound either to the cell wall fraction or to the organelles. Gel filtration of the soluble fraction showed Cd to be associated mainly with 5,000 to 10,000 molecular weight components in roots, and 700 to 5,000 molecular weight components in leaves. Small amounts of Cd were found in the high molecular weight proteins (molecular weight 150,000). Only traces of Cd could be detected as a free ion. Chemical characterization of the low molecular weight components resulted in the identification of nine amino acids which were identical in roots and leaves. Cd in bean plants is assumed to be bound to peptides and/or proteins of low molecular weight.